Pencarian Identitas Diri Tokoh Utama dalam Novel Dayon Karya Akmal Nasery Basral Kajian Psikologi Sastra - Gebryla Rito; M. Yusuf; Zurmailis Zurmailis (Puitika, 2023)
This study discusses the search for the main character's identity in the novel Dayon by Akmal Nasery Basral which is motivated by the problem of changing the name that occurs to the main character. This study uses a Literary Psychology approach. This study aims to explain how the process of searching for the main character's identity in the novel Dayon by Akmal Nasery Basral and to explain whether the process of searching for self-identity is influenced by the author's desire. The theory used in this study is the theory of Psychoanalysis by Jacques Lacan which divides the stages of the subject's self-development based on three aspects, namely imaginary, real, and symbolic. The method used is the Lacanian Psychoanalysis method which sees language as a sign indicating the author's desire. From the research that has been carried out, the process of searching for the main character's identity begins when the main character enters school age, to experience repeated traumatic experiences that occur to the main character, then the search for the main character's identity occurs until the main character identifies himself with Others. Then, the author's desire influences the search for identity carried out by the main character in the novel Dayon by Akmal Nasery Basral. The author's desire arises unconsciously through the language set forth in literary works. The findings of this study are that the main character has not been able to provide complete confirmation regarding self-identity because it is still in the unfinished search stage.